2014
DOI: 10.1016/j.procir.2014.07.136
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment through In-process Monitoring of Wire-EDM for Fir Tree Slot Production

Abstract: Against the background of an increased importance of in-process quality measurement -especially for manufacturing of safety critical jet engine componets -this paper deals with the development of a process monitoring tool for process quality assessment and correlating surface integrity evaluation of Wire-EDM for fir tree slot production. For the last trim cut, which is the relevant cut for the final surface integrity, a correlation between process data and surface integrity aspects is set up. The process data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In finishing, on the other hand, it depends on the intensity of the discharge current peak, the feed rate and, to a lesser extent, dielectric flow rate into the working gap. Klocke et al [18] investigated the use of Topas plus X (TPX) and AGN3C -(AG) coated electrodes in comparison to a standard brass electrode. The authors found that the use of coated electrodes increases the surface roughness Ra in relation to the surface machined with a brass electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In finishing, on the other hand, it depends on the intensity of the discharge current peak, the feed rate and, to a lesser extent, dielectric flow rate into the working gap. Klocke et al [18] investigated the use of Topas plus X (TPX) and AGN3C -(AG) coated electrodes in comparison to a standard brass electrode. The authors found that the use of coated electrodes increases the surface roughness Ra in relation to the surface machined with a brass electrode.…”
Section: Introductionmentioning
confidence: 99%
“…However, the location of areas with the highest electrical field strength is also affected by contamination of the dielectric fluid in the IEG by electroconductive particles, which are produced during the EDM process [25][26][27][28]. The distribution of dispersed contaminants over the IEG volume is random and depends on a number of factors including the IEG dimensions [23,29,30], the applied voltage [30,31], the pulse frequency and duty cycle of the discharges [30][31][32][33][34], the workpiece and tool materials [33], the speed, at which the dielectric fluid (typically mineral oil) is pumped [30,35], the thickness of the workpiece being processed and the size of particles being removed from the IEG [35,36]. To ensure the stability of the ED process, it is necessary to maintain the removal of contaminants from the dielectric fluid at a rate that is no less than that at which the new electroerosion products contaminating the IEG are produced [35].…”
Section: Introductionmentioning
confidence: 99%
“…This technology allows for the processing of difficult-to-cut, extremely hard materials with very tight tolerances and with impressive surface finish [ 2 , 3 ]. Nonetheless, trial and error approaches are still required for process optimization due to the above-mentioned limited accuracy of theoretical models [ 4 ]. In this context, artificial intelligence (AI) and more specifically, deep learning (DL) techniques appear to be an interesting approach, provided that massive amounts of data can be collected from the process.…”
Section: Introductionmentioning
confidence: 99%